Studi Etnografi Proses Pendidikan Karakter pada Anak Usia Dini melalui Dendang Saluang - Hidayati, Isa; Lubis, May Sari; Qalbi, Zahratul (THUFULA, 2021)
This study aims to see the process of character education for early childhood through dendang saluang in Nagari Saribu Rumah Gadang, Solok Selatan. This type of research is qualitative with an ethnographic approach. Analysis of the data used is the Spradley model. The research data obtained by observation, documentation and interviews. The results of this study indicate that the process of character education through dendang saluang consists of 3 processes are moral knowing, feelings about morals and moral behavior. Dendang Saluang will be a media character education for early childhood when this process are carried out during the Dendang Saluang activity.